What’s on the menu today? First report of nectarivory for Rhynocoris cuspidatus (Hemiptera: Reduviidae) - Pizarro-Borrull, Maria; Alamo, Mario (Fragmenta entomologica, 2025)
This study reports the first observation of nectarivory in the predator reduviid Rhynocoris cuspidatus (Ribaut, 1921) in Spain. One individual of R. cuspidatus was observed sucking nectar from a Jacobaea vulgaris Gaertn. inflorescence in a grassland meadow in Berrecil de la Sierra (Spain). Our observation suggested that R. cuspidatus can use floral resources to obtain sugar or moisture during extreme climate conditions, such as can occur during Mediterranean summer.